The circular economy in urban projects: A case study analysis of current practices and tools (Transactions of the Association of European Schools of Planning, 2021)
Over the last decade, the concept of the circular economy (CE) has gained momentum among practitioners, politicians, and scholars because of its promise of achieving sustainability goals. However, there is still a need to demonstrate and assess the positive environmental impacts of the CE. With respect to the building sector, the CE is still a relatively new topic. To date, research has tended to focus primarily on the macro-scale (cities or eco-parks) and the micro-scale (manufactured products or construction materials). Nevertheless, the often-neglected built environment is also expected to play a crucial role in the transition towards a CE due to its high contribution to various environmental burdens. This paper contributes to this growing area of research by reviewing four cases of ‘circular neighbourhood’ projects in Europe. First, a conceptual framework analysis is defined and applied to the cases. Second, CE initiatives and actions are identified and classified using interviews and document analysis. Third, the use of assessment tools within these CE projects is investigated. The results demonstrate a diverse representation of the CE paradigm and the growing role played by the assessment tools.
Keywords: circular economy; life cycle assessment; urban project; circular neighbourhood